Erratum: Agrarian Conflict in the Gunung Leuser National Park Area by the Aceh Refugee Community - Editor (Journal of Peasants' Rights, 2023)
This article has been retracted by Publisher based on the following reason : Requested by Author, because there is unethical data to publish.